Design of a Printing Production Cost Information System Using the Activity Based Costing Method - H, Rizky Putra Perdana; Yasin, Verdi; Sianipar, Anton Zulkarnain (Universitas Mohammad Husni Thamrin, 2025)
In an era of increasingly competitive business competition, the use of information technology has become a crucial aspect in supporting the efficiency and effectiveness of company operations. Especially for companies engaged in the manufacturing sector, accurate management of production costs is an important basis for determining selling prices and maintaining competitiveness in the market. Increasingly fierce business competition demands companies to have an efficient and accurate cost management system, especially in the manufacturing industry. PT Anggadarma Kalimusada, as a printing company, faces challenges in calculating production costs accurately because it still uses manual methods. This study aims to design a web-based production cost information system by applying the Activity Based Costing (ABC) method to improve accuracy in determining the cost of goods manufactured. The research method used is descriptive qualitative with a Waterfall model software development approach. The system was developed using the PHP Laravel framework and a MySQL database. The research results show that the system is capable of identifying activities, allocating cost drivers, and accurately calculating production costs per unit. The system also provides features for activity input, cost driver recording, production cost calculations, and cost of goods manufactured reports. By implementing the ABC method, this system provides more representative cost information and serves as a basis for managerial decision-making. This system is expected to help companies improve efficiency, transparency, and accountability in managing production costs.